Understanding productivity: A review of recent technical research - Richard Dion; Robert Fay (Bank of Canada, 2008)
The authors provide an extensive review of the rapidly expanding research on productivity, both at the macro and micro levels. They focus primarily on papers written about Canada, but also draw on selected studies from other countries, especially the United States, where such work sheds important light on particular aspects of productivity growth. The authors extract the key results of the studies and signal important methodological features that underpin those results. They also identify areas for further research.
Keywords: D24; O31; O40; O47; 330; Productivity; Technischer Fortschritt; Informationstechnik; Volkswirtschaft; Produktivität; Kanada; USA